A Study To Assess Psychological Status And Behavioural Changes Among HIV/AIDS Affected Orphans-A Cross Sectional Study - Dr Pavan Kulkarni; Dr Sudha Bala; Dr Sushma Katkuri; Dr Deeksha Tiwari; Dr Rajit Pokkula; Dr Rishabh Chormalle; Dr Shrikanth Muralidharan (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: There are near about 153 million children who have had at least one parent die according to policy makers globally and they are struggling to find care solutions. Various psycho-social implications on children such anger, fear, anxiety, depression, grief, guilt and shame, lack of interest in surrounding, loss of confidence, complaining that no one loves, feeling worthless or inferior to others suicidal tendencies, lower cognitive abilities and other behavioural problems. Aims & Objectives: To evaluate psychosocial status and behavioral problems among HIV affected orphan children. Materials & Methods: It was a cross sectional study conducted for a period of 2 months on HIV affected orphans in a NGO of Hyderabad. Results: Psychological status of the study participants was good and strong. Only 10% of the study participants were depressed and very fewer in number such as 13.3% were scared about the situation. Near about 26.6% of the study participants at times get angry and 20% of the study participants feels lonely. Conclusion: The mental status of the study participants was marginally poor while majority of the study participants were mentally strong enough to cope up with the day to day life. They had a very good support from the care takers that was very appreciable thing.